Toward strategic green ICT policy to eliminate environmental problems - Hameed, Shihab A.; Khalifa, Othman Omran (2011)
Due to climate change; global environmental problems are affecting directly many countries’ energy and industrial policies. It is estimated that the ICT consumption of energy will be about 15% of the total consumption worldwide in 2020. Increasing energy consumption leads to serious of environmental disruption. Therefore, many countries are establishing Green ICT (Information Communication Technology) policies which increase energy efficiency due to correspondence climate change. Therefore, the governments especially in third world need to have policies and strategies for efficient energy use in IT. The purpose of this study is to present the current problems related to green ICT and the effort spend to solve it. Recent studies are emerging regarding the energy consumption paradigm, based on newly changed IT practices. This study is a preliminary framework regarding policy direction of Green ICT based on a new paradigm. It provides guidelines for decision makers and ICT professionals to enhance their work toward eliminating environmental problems. It shows the role of ICT and its equipments in Green environment as well as its indirect role through ICT applications to enhance performance of other sectors toward green environment. Therefore, this study can be used as an initial model to accomplish reasonable strategic green ICT policy to serve the world especially the third world countries.